Palisade Cartilage Myringoplasty - Bhattarai, H (Nepalese Journal of ENT Head and Neck Surgery, 2012)
Nepalese Journal of ENT Head and Neck Surgery Vol.2 No.1 Issue 1 (Jan-Jun 2011) 36-37 DOI: http://dx.doi.org/10.3126/njenthns.v2i1.6787